Semiotics Performance in The Poem “Tentang Mata” and “Tentang Mata Pula” By W.S. Rendra - Padmasari, Arumtyas Puspitaning; Nensy Megawati Simanjuntak; Victor MTL Tobing (PT FORMOSA CENDEKIA GLOBAL, 2024)
Literary works are created to be enjoyed and appreciated by society. The formulation of the research argues about the language style, vocabulary, and intended meaning of the poem “Tentang Mata” and “Tentang Mata Pula” by W.S. Rendra. This research is to obtain a clear picture of the poem “Tentang Mata” and “Tentang Mata Pula” through a stylistic approach. The benefits of this research contribute to the development of linguistics applied and linguistic analysis from literary works, provide insight to scholars on how to conduct linguistic analysis of literary works, and become alternative teaching materials for language and literature teachers. The research approach uses a descriptive qualitative method in literature in line with stylistics. The research data were analyzed using data collection techniques involving the steps of data identification, data classification, and deductive data interpretation. The results of the research describe the conditions and situations that occurred in 1998, with the emergence of many connotative words in raising the issue of fate and living conditions, from poverty. In addition, it is presented that society itself is only chasing dreams by creating conditions and situations that are already disproportionate